GIPANG CASSAVA MARKETING STRATEGY (CASE STUDY ON IKM IKA-KE IN PURWAKARTA DISTRICT, CILEGON CITY) - Suherna suherna; Dian Anggraeni; Dini Kartika Sari (Syarif Hidayatullah State Islamic University Jakarta, 2022)
Gipang cassava is an innovation of one of the local foods from Cilegon, gipang is a traditional food usually made of glutinous rice (one of the rice varieties that only can be found in Asia), peanut, and caramel is one of the local foods from Cilegon. IKA-KE SMI is one of those gipang cassava industries in Cilegon. The food industry is one of the most popular industries. Each industry holds one's own to serve the best product. This research purpose is to analyze the internal and external factors of IKA-KE SMI, formulate alternative strategies that are appropriate to be implemented by IKA-KE SMI, and specify the best alternative strategy for IKA-KE SMI. Data analysis using Matrix IFE and EFE, IE Matrix, SWOT Analysis or SWOT Matrix and QSPM Matrix. The result shows that internal factors have 8 strengths and 6 weaknesses, and external factors have 7 opportunities and 4 threats. Matrix IE shows IKA-KE SMI is in cell II position means that it's in growth and built condition. SWOT Matrix formulate 8 alternative strategies for IKA-KE SMI and QSPM Matrix shows the most recommended alternative with the highest TAS value for IKA-KE SMI to improve promotional campaign and improve online business with a TAS value of 6.825.